OC-049 A prospective comparison of safety and tolerability of propofol versus standard sedation for double balloon enteroscopy– time for a push forward?. (22nd June 2015) - Branchi, F; Sanders, DS; Turnbull, D; Eapen, G; Jankowski, S; Sidhu, R
Abstract : Introduction: Double balloon enteroscopy (DBE) is routinely performed with moderate sedation in the UK. However, in comparison to standard endoscopy, DBE is complex and takes longer, therefore deep sedation with propofol could improve tolerability and feasibility of the test. Method: All patients undergoing DBE between March13 and October14 were prospectively enrolled. DBE was performed either with administration of sedation with fentanyl and midazolam or with anaesthetist-assisted deep sedation with propofol, the decision being made on the basis of patients' clinical history and expected length of the test. Data from patients receiving propofol were compared to those from patients receiving standard sedation during the same period. Patients were asked to fill in a questionnaire regarding their expectations before the test and their satisfaction afterwards. Anxiety, pain and discomfort were assessed by means of validated numeric rating scales (NRS, range 0–10). Data on comorbidities, previous surgery and hospital anxiety and depression scores (HADS) were also collected. The procedural characteristics of DBE were assessed. Results: Twenty-one DBE (18 oral, 3 anal, 33% male) were performed with the aid of propofol infusion and 67 (54 oral, 13 anal, 51% male) with standard sedation. Mean age was 48 ± 14.3 in the propofol group and 58.6 ± 15.9 in the sedation group (p = 0.012). There were no other differences in demographics, comorbidities or HADS scores between the groups. The indications for DBE included obscure gastrointestinal bleeding (n = 45), Peutz-Jeghers syndrome (9) and suspected Crohn's disease (20), small bowel tumour (10) or celiac complication (2). The mean dose of propofol administered was 1123 ± 483 mg. The mean doses of midazolam and fentanyl were 6 ± 3 mg and 118 ± 54 mcg respectively. No differences were observed in terms of diagnostic yield (52% vs 57%, p = ns) and therapeutic yield (33% both groups). Patients in the propofol group reported lower scores of pain (median score 0, IQR 0–0.5 vs 3, IQR 0–6, p < 0.0001), discomfort (median 0, IQR 0–0.5 vs 3, IQR 1–7, p < 0.0001) and distress (median 0, IQR 0–0 vs 1, IQR 0–5, p = 0.001) during the procedure. Whilst there were no complications in the propofol group, there was one episode of oxygen desaturation in the control group. Conclusion: The use of propofol for DBE has a good safety profile and better patient tolerability and satisfaction in comparison with moderate sedation. It is associated with a high diagnostic and therapeutic yield. Its use should be recommended when the procedure is expected to be longer and technically challenging. Disclosure of interest: None Declared.